Guatemala : Ex-Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2011)
Owing to the deteriorating economy of Guatemala, authorities requested a Stand-By Arrangement (SBA) with access of SDR 630.6 million in April 2009, which aimed at safeguarding macroeconomic and financial stability and anchoring investor confidence. Executive Directors have agreed that the SBA is successful in mitigating the financial crisis. Directors have appreciated the authorities' commitment in implementing policies focused on short-term macroeconomic and financial stability on time, and also have urged to look into some important vulnerabilities that would have strengthened the fiscal framework.